Brain Integrity Changes Underlying Cognitive and Functional Recovery Postliver Transplant Continue to Evolve Over 1 Year. Issue 3 (March 2018) - Ahluwalia, Vishwadeep; Wade, James B.; White, Melanie B.; Gilles, HoChong S.; Heuman, Douglas M.; Fuchs, Michael; Gavis, Edith A.; Fagan, Andrew; Thacker, Leroy R.; Sterling, Richard K.; Stravitz, Richard Todd; Puri, Puneet; et al.
Abstract : Background: There is evidence of brain recovery on brain magnetic resonance imaging (MRI) early postliver transplant (LT), but the longer-term impact is unclear. The aim of this study was to determine the change in brain MRI parameters, cognition, and health-related quality of life (HRQOL) between 6 and 12 months post-LT. Methods: Listed cirrhotics underwent cognitive, HRQOL and brain MRI pre-LT, 6 months (post-LT1), and 1-year (post-LT2) post-LT. Assessment of MRI changes between visits was performed for ammonia-associated metabolite changes using magnetic resonance spectroscopy, white matter changes using tract-based spatial statistics analysis on diffusion tensor imaging data and grey matter changes using voxel-based morphometry analysis on 3D high resolution T1-weighted images. Results: Forty-five patients were included, of which 23 were tested at all visits. Cognitive and HRQOL scores improved between all visits compared with pre-LT values. This trend continued on magnetic resonance spectroscopy with reduced glutamine + glutamate and higher myoinositol, choline between pre-LT/post-LT1 but lower degrees of improvement between post-LT1/post-LT2. On diffusion tensor imaging, mean diffusivity, linear diffusivity and mode of anisotropy continued to increase in the posterior internal capsule at both post-LT visits. On voxel-based morphometry, a continued increase was seen in basal ganglia grey matter between both post-LT visits was seen. Conclusions: HRQOL and cognition continue to improve compared with pre-LT values up to 1 year post-LT, although the rate of improvement slows down after 6 months. Grey matter increase is steady over time at 1 year although changes in ammonia-related metabolites and white matter integrity improve at a slower pace at 1 year post-LT. Abstract : The authors of this study show that the significant improvements seen in cognition, quality of life, brain metabolites and brain structures at 6 months post-LT continue to evolve, but at a slower pace, between 6 and 12 months posttransplantation. Supplemental digital content is available in the text.